2014
DOI: 10.4103/0255-0857.142233
|View full text |Cite
|
Sign up to set email alerts
|

Future of diagnostic microbiology

Abstract: Diagnostic Microbiology is the tool that makes it possible to identify the exact etiology of infectious diseases and the most optimal therapy at the level of individual patients as well as communities. Conventional methods require time to grow the microbes in vitro under specific conditions and not all microbes are easily cultivable. This is followed by biochemical methods for identification which also require hours and sometimes days. Transport of the specimens under less than ideal conditions, prior use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Many genes and gene mutations are known to be associated with bacterial pathogenicity or antibiotic resistance [42,43]. We performed a search for such genes in the examined ancient strains to elucidate whether these genes were present in Staphylococcus genomes 3 million years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Many genes and gene mutations are known to be associated with bacterial pathogenicity or antibiotic resistance [42,43]. We performed a search for such genes in the examined ancient strains to elucidate whether these genes were present in Staphylococcus genomes 3 million years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 19th century, the gold standard for the detection of bacterial infection has been the cultivation of bacterial pathogens from blood or tissue samples. 12 Despite findings of a relationship between bacterial infiltration and sVHD, verification using microbiological culture is not a routine clinical method in this patient population. 13 Giladi and colleagues, 14 Chuard and colleagues, 15 and Campbell and colleagues 16 isolated bacteria from the heart valves in 11% to 17% of sVHD patients, but lacking structural and ultrastructural validation, they concluded that this was a contamination.…”
Section: Perspectivementioning
confidence: 97%
“…2). Данное распределение хорошо отражает общероссийские и общемировые тенденции по закономерному включению молекулярно-генетических методов в набор инструментов бактериологической (микробиологической) лаборатории [5,6]. Таким образом, по нашему мнению, следует учитывать технологическое развитие отрасли в этом направлении и уделять этим методам особое внимание как в рамках модернизации нормативной базы (в том числе включение некоторых современных методов в стандартный арсенал работы микробиологов), так и содействуя расширению образовательной программы для микробиологов по изучению данных методик.…”
Section: комитет помикробиологииunclassified